Handbook of psychodermatology - Latheef, Abdul EN.; Prabhu, Smitha S (b)
A multidisciplinary handbook covering clinical patterns in psychodermatology, psychoneuroimmunology, psychological aspects of cosmetic dermatology, sexually transmitted diseases, geriatric and adolescent issues, Hansen$1 (Bs disease, psychological interventions (meditation, CBT, family therapy), psychopharmacology, liaison clinic, and research in psychodermatology. s
Keywords: Psychodermatology; Dermatology; Psychoneuroimmunology